The Effect of Compensation and Work Environment on Employee Job Satisfaction at PT. PITS (Pembangunan Investasi Tangerang Selatan) - Takeshi Bima Syukur; Muhammad Yusuf (Buletin Ekonomika Pembangunan, 2025)
This research examines the influence of Compensation and work environment on employee job satisfaction at PT. PITS. The background of this study is based on the importance of internal company factors, such as fair Compensation and a conducive work environment, in enhancing employee satisfaction. A quantitative associative approach was used, with data collected through questionnaires distributed to 50 employees. The research method employed path analysis using SPSS 25. The results revealed that compensation and work environment positively and significantly impact job satisfaction. These findings suggest that improving employee welfare through appropriate Compensation and a supportive work environment contributes to greater job satisfaction, which is critical to organizational success. Keywords: Compensation, Work Environment, Job Satisfaction, Employee         Welfare, PT. PITS